Isolation and Characterization of a Heavy Metal-reducing Pseudomonas sp. strain Dr.Y Kertih with the Ability to Assimilate Phenol and Diesel - Kesavan, Veeraswamy; Mansur, Abdulrasheed; Suhaili, Zarizal; Salihan, Mohd Syahmi Ramzi; Rahman, Mohd Fadhil Abd; Shukor, Mohd Yunus (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
The indiscriminate released of heavy metals and xenobiotics into soils and aquatic bodies severely alter soil organisms and the ecosystem. The isolation of xenobiotics degrading microorganisms is cost-effective and naturally pleasant approach. Lately, the toxicological effect of molybdenum to the spermatogenesis of several organisms has been record. This present study is aimed at the isolation and characterization of a bacterium capable of converting molybdenum to the colloidal molybdenum blue. Bacteria characterization was performed in a microplate format using resting cells. Thus, the reduction process can be employed as a device for molybdenum bioremediation. The results of the study revealed an optimum reduction at pH between 6.0 and 6.3 and temperatures of between 25 and 40 oC. Similarly, it was also observed that a phosphate concentration not greater than 5.0 mM and a sodium molybdate concentration at 20 mM was required for reduction. Glucose was observed as the best carbon source to support reduction. Following the scanning of molybdenum blue, it revealed an absorption spectrum indicating the characteristics of molybdenum blue as a reduced phosphomolybdate. Molybdenum reduction is inhibited by heavy metals like silver, lead, arsenic and mercury. Furthermore, the ability of the bacterium (Pseudomonas sp. strain Dr.Y Kertih) to utilize several organic xenobiotics such as phenol, acrylamide, nicotinamide, acetamide, iodoacetamide, propionamide, acetamide, sodium dodecyl sulfate (SDS) and diesel as electron donor sources for aiding reduction or as carbon sources for growth was also examined. Finding showed that none was capable of aiding molybdenum reduction, however the bacterium was capable of growing on both diesel and phenol as carbon sources. GC analysis was used to confirmed diesel degradation.